Field erosion by wind as indicated by fluctuations in the ash content of Sphagnum peat - I. Vuorela (Bulletin of the Geological Society of Finland, 1983)
The ash content curves for three Sphagnum peat profiles were correlated with those for Cerealia and the natural indicators of bare mineral soil. The fluctuations in the ash values seem to indicate erosion of fields by wind as a result of tilling and other activities in cultivated fields. The increase in these values in the uppermost samples is an even better indicator of improvements in agriculture than are the curves for Cerealia and weeds, which decrease together with the small pollen production of the recently dominant crop species and advances made in agricultural technology. The local pre-agrarian cultural phases revealed by the C14 datings and the tree pollen data cannot be documented by the ash content values of the Carex peat profiles.